Source and Fate of Dissolved Black Carbon in the Western South China Sea During the Southwest Monsoon Prevailing Season. Issue 11 (6th November 2017) - Fang, Ziming; Yang, Weifeng; Chen, Min; Ma, Haoyang
Abstract: Dissolved black carbon (DBC) is of importance for understanding the marine carbon cycle especially on long time scales owing to its refractory nature in the dissolved organic carbon pool. However, its geochemical behavior is poorly understood in the open oceans due to limited DBC data. Here 86 seawater samples were determined using the benzene‐polycarboxylic acid method to investigate the source and fate of DBC in the western South China Sea. The DBC concentration varied from 0.49 to 1.60 μmol L −1, averaging 0.95 μmol L −1 . Spatially, the Mekong River plume (i.e., MR plume) showed higher DBC concentrations and (B6CA + B5CA)/(B4CA + B3CA) ratios (i.e., R H / L ) in the mixed layer than the distal regions. In addition, the DBC concentration positively correlated with salinity in the mixed layer within the MR plume, indicating the important DBC input from the Mekong River. In intermediate water (500–1500 m), DBC varied from 0.70 to 0.85 μmol L −1 and the R H / L value continually increased with depth, implying another DBC source with distinct R H / L ratio comparing with the euphotic zone. Based on a conservative mixing model, the Mekong River and atmospheric deposition collectively input 38–100 Gg DBC each year, and over one third of DBC were removed within the euphotic zone, probably via photodegradation and/or adsorption on particles. These results highlighted the different DBC behavior in the euphotic and intermediate zones and lent support to DBC as a proxy for tracing water mixing in the intermediate and deep oceans. Key Points: The Mekong River discharge is the major source of DBC in the western South China Sea Over one third of river‐ and atmosphere‐derived DBC are removed within the euphotic zone, probably via photooxidation The BPCA composition seems to record the water mixing in the intermediate layer in the western SCS